Assessment of Vegetation Degradation: Status of Methodological Research - Kumar, Suresh (Annals of Arid Zone, 2016)
Vegetation degradation manifests itself at plant. community and regional levels. Basic parameters at the plant level viz. habit, vigour, yield, litter, and seed bank; at the community level, viz. botanical composition, plant density, dominance, cover and extent, biomass and carrying capacity. quality and palatability, ecological status, age distribution and finally at the regional level viz. biological spectrum, dominance-diversity relations and stability, resilience, equilibrium status are discussed. Using these parameters a score card has been devised and presented in the paper for assessing degradation of vegetation.